PENERAPAN SOSIO-PSIKOLINGUISTIK DALAM PEMBELAJARAN BAHASA ARAB - Zahra Silmy Damanik, Nissa; Nasution, Sahkholid (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
The application of socio-psycholinguistics in Arabic language learning aims to optimize understanding and mastery of the language through an approach that integrates social and psychological factors. The application of socio-psycholinguistics in Arabic language learning is very important to enrich students understanding of language as a communication tootl that is not only limited to grammatical structure or vocabulary. Socio-psycholinguistics studies the relationship between language, individuals, and society, as well as how the influence of the social environment and psychological conditions affect the way language is learned and used. In the context of Arabic, this approach is highly relevant because the language has variations depending on social and cultural contexts and is used in both formal and religious communication. By understanding these aspects, learners can more easily adapt in speaking, writing, and comprehending Arabic in various situations, whether in academic, social, or religious contexts. The integration of socio-psycholinguistics can create a more contextual and profound learning experience, as well as enhance effective communication skills.